ChemInform Abstract: Highly Selective 1, 4‐ and 1, 6‐Addition of P(O)—H Compounds to p‐Quinones: A Divergent Method for the Synthesis of C‐ and O‐Phosphoryl Hydroquinone Derivatives. Issue 22 (13th May 2013) - Xiong, Biquan; Shen, Ruwei; Goto, Midori; Yin, Shuang‐Feng; Han, Li‐Biao
Abstract C‐ and O‐phosphoryl hydroquinone derivatives are prepared selectively by employing different additives.